Common Patterns and Pedagogical Implications of Code-Switching and Code-Mixing in Multilingual Learners: A Systematic Literature Review - Susiawati, Iis; Azkiyah, Siti Nurul; Wahab, Muhbib Abdul; Maswani, Maswani (Langkawi: Journal of The Association for Arabic and English, 2025)
This study aims to identify the common patterns of code-switching and code-mixing employed by multilingual learners and their pedagogical implications. Using a systematic literature review method, 44 empirical studies published between 2019 and 2024 were selected from Scopus and Google Scholar databases. The findings reveal seven dominant forms of code-switching and code-mixing, including intra-sentential, inter-sentential, tag-switching, intra-word switching, situational, metaphorical, and code-mixing. These patterns are shaped by three primary factors: social context, learning environment, and cultural identity. Pedagogically, these linguistic strategies play a crucial role in enhancing comprehension, developing language skills, supporting cultural identity, fostering flexibility, and increasing engagement in multilingual classrooms. However, excessive use without guidance may lead to confusion and hinder language development. The study highlights the importance of understanding these practices for designing inclusive and effective language education strategies. It contributes to sociolinguistics and multilingual pedagogy by offering practical insights for teachers, curriculum developers, and education policymakers. Additionally, this review sheds light on emerging digital communication trends, such as the use of code-switching and code-mixing in online platforms and blended learning environments. It also provides actionable suggestions for integrating these strategies into teacher training and curriculum development. By addressing both linguistic and pedagogical aspects, the study underscores the relevance of language alternation in contemporary education.